Does HAART dysregulate angiogenesis in HIV infected preeclampsia? (Nigerian Journal of Physiological Sciences, 2022)
A dysregulation of angiogenic mediators has been implicated in HIV infection. Inconsistent data exists on highly active antiretroviral therapy (HAART) usage in pregnancy and its association with PE development. In view of the high prevalence of HIV infection and PE in SA, this study was aimed at determining PlGF and sFlt-1 levels in HIV-infected normotensive and preeclamptic pregnancies treated with HAART. Both PlGF and sFlt-1 were quantified in serum from HIV positive [normotensive (N+) and preeclamptic (P+)]; and HIV negative [normotensive (N-) and preeclamptic (P-)] pregnancies, using a Milliplex Multiplex immunoassay. sFlt-1 was significantly upregulated in P+ vs the N+ groups. PlGF was significantly downregulated in PE vs normotensive groups, regardless of HIV status. sFlt-1/PlGF ratio was significantly increased in PE- vs the N- groups. We report an amplification of sFlt-1 in lieu of PlGF down-regulation in HIV-infected pregnancies receiving HAART.